GAMBARAN TINGKAT KECEMASAN PRA GENERAL ANESTESI PASIEN AMBULATORY PADA TINDAKAN ENDOSKOPI DI RSUD Dr SOETOMO SURABAYA - Kurniawan Ariesyono; Amin Susanto; Ema Wahyu Ningrum (Jurnal Cakrawala Ilmiah, 2024)
Implementation Comprehensive examination is the first and last step in ambulatory anesthesia. Objectives for the overall research At Dr. Soetomo Hospital Surabaya, ambulatory individuals underwent action endoscopy under general anesthesia in order to determine the characteristics of age, gender, and education. Examine This study type is descriptive in nature. 63 people in a sample had ambulatory endoscopy for examination while under general anesthesia. Consecutive sampling is a non-probability sampling device used in data collecting. analysis with a univariate analysis. Analysis and discussion findings may be removed. In summary The respondents' characteristics included a majority age of 46 to 70 years, a level of concern light for those aged 53 to 70 years, and a level of worry heavy for those aged 18 to 35 years (20.6%). The level of anxiety category weight was 52.4 percent. Male gender _ (58.7%) with degree of concern